Rheological behaviour of erythrocytes in patients with diabtes mellitus. - Huang, Hong. (2013)
Diabetes is associated with many comorbid pathologies that lead to increased morbidity and mortality. Rheological behaviors on RBC changes in diabetes are currently investigated as one of the risk factors for many complicating diseases. The aim of this study is to present the difference on RBC deformability, cell membrane stability and RBC aggregation between diabetics and normal. This study contains ten diabetic patients and normal volunteers. RBC rheological properties were examined by LoRRCA MaxSis. LoRRCA MaxSis use the method of ektacytometry and syllectometry to measure the RBC elongation and aggregation parameters. The results showed that decrease in EI value with increasing shear stress on the deformability test, and increased AMP and AI as well as decreased t1/2 on RBC aggregation test. Hence, it can be concluded that the RBC from diabetes show increased deformability, and aggregation when compared to normal healthy individuals.